Chapter 10 Shakespeeding into Macbeth and The Tempest Teaching with the Shakespeare Reloaded Website - Semler, Liam E. (Taylor & Francis, 2019)
The Australian "Better Strangers" project has begun exploring the potential of gamified learning scenarios to enrich teacher professional development and student learning at high school and university. In May 2016, Shakeserendipity became the subject of an unsolicited newspaper review by 16-year-old South Australian student Dylan Carpinelli. Australian high school teacher Catherine Hicks shared the Macbeth Shakespeed module with her Year 12 class in North Queensland as part of a larger learning activity. Students were to write a memoir from the perspective of a minor character in Macbeth and Hicks used Shakespeed "as an activity to help them brainstorm the themes and ideas and create modern interpretations of the play." In the Macbeth Shakespeed game the Wild Card is a YouTube audio clip of the song "Metaphor" by Swedish alternative metal band In Flames. The song's persona reflects on the pain, sickness, and entrapment of his desire.